Metabolism of eriocitrin in the gut and its regulation on gut microbiota in mice - Meng, Xia; Wu, Hongchen; Xiong, Jiayi; Li, Yongquan; Chen, Lin; Gu, Qing; Li, Ping (Frontiers in Microbiology, 2023)
Eriocitrin, found in lemon fruit, has shown a wide range of biological properties. Herein, to evaluate the intestinal metabolic profile of eriocitrin in colon, the flavonoids in mice colon contents were identified by ultra performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UPLC-ESI-MS/MS), and a total of 136 flavonoids were found, including eriocitrin and its six metabolites (eriodictyol, homoeriodictyol, hesperetin, eriodictyol-3'-O-glucoside, hesperetin-7-O-glucoside and eriodictyol-7-O-(6''-O-galloyl) glucoside). Mice colon contents were used for 16S rDNA gene sequencing and gas chromatography-mass (GC-MS). Result showed that dietary intervention of eriocitrin significantly alters the beta diversity of the gut microbiota, the probiotics such as Lachnospiraceae_UCG_006 were significantly enriched, and the production of butyrate, valerate and hexanoate in the colon pool of short-chain fatty acids (SCFAs) were significant increased. The spearman's association analysis performed some intestinal bacteria may be involved in the metabolism of eriocitrin. Collectively, our results preliminarily suggest the metabolism of eriocitrin in the gut, demonstrating alterations of eriocitrin in gut microbiota, which warrants further investigation to determine its potential use in food and biomedical applications.